One-pot process for the conversion of aroyl chlorides to acyl thioureas - Ramana, Chepuri V.; Senthilkumar, B. (WO2014087431A1, WO2014087431A8, 2013)
The present invention disclose an improved one pot process for synthesis of acyl thioureas of formula (I), with yield greater than 80%, from aroyl chlorides of formula (I) wherein, R′ is an aryl or a heteroarylene group substituted with one or more groups selected from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino, carboxyl, ester, halogenated hydrocarbon or an aryl or heteroaryl; R″ and R′″ are selected independently from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino or halogenated hydrocarbon.